KEARIFAN LOKAL DALAM MANTRA MASYARAKAT SAMIN DI DUSUN JEPANG DESA MARGOMULYO KECAMATAN MARGOMULYO KABUPATEN BOJONEGORO - Syaiful Rizal, Maulfi (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This study aimed to describe the value, functionality, and local wisdom in Mantra Naklukno Sedulur Papat. The data source of this research is the book of spells possessed by the Samin people in Margomulyo village, Margomulyo District of Bojonegoro. Besides the book of spell, as the source of data, this study also used the interview technique to determine the function of these spells for its users that is Samin community from Margomulyo village, the District of Margomulyo, Bojonegoro. The research found that form the three spells analyzed, namely naklukno sedulur papat, kanggo wong mati, and panen or wiwit panen, there are local wisdom in it. The value of Javanese culture, which is contained in the spells are the java religious value and Java philosophical value. The Java religious value appears in the form of submission and trust in God, to ask for help to God, while the existing philosophical value of Java are doing the right thing and the right to stay away from four forbidden cases. The functions of these spells is as an educational tool for members of the community. The local wisdom, which is still exist are still believing and uphold the principles of sedulur papat limo pancer with the addition of Islamic culture.